PROBIOTICS FOR IRRITABLE BOWEL SYNDROME : A SYSTEMATIC REVIEW - Stevenie (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
It has been demonstrated that dysbiosis, also known as imbalances or aberrations of microbiota, plays a significant role in FGIDs and allergens, including infection and antibiotic-associated diarrhea, food allergy, atopic eczema, inflammatory bowel syndrome, and irritable bowel syndrome. It has been demonstrated via research that the mechanisms of action of probiotics in irritable bowel syndrome are diverse, heterogeneous, and strain specific. For the purpose of understanding irritable bowel syndrome (IBS), the mechanism of action of probiotics has to be translated into a language that is more comprehensible from a clinical and a practical standpoint. The competitive exclusion mechanism of pathogens by luminal pH, competition for nutritional sources, and production of bacteriocins, SCFAs, and biosurfactants are all involved in the modulation of the gut microbiota. These factors all work together to prevent the proliferation of pathogens and inhibit their adhesion to the gut epithelia. Because the use of synbiotics as an alternative treatment for IBS is still in its infancy, and because the outcomes of synbiotic administration may be dependent on the probiotic component of the synbiotic, greater emphasis should be placed on determining patients' probiotic responses before beginning treatment with synbiotics.